2022
DOI: 10.1109/access.2022.3151641
|View full text |Cite
|
Sign up to set email alerts
|

Tasmanian Devil Optimization: A New Bio-Inspired Optimization Algorithm for Solving Optimization Algorithm

Abstract: In this paper, a new bio-inspired metaheuristic algorithm called Tasmanian Devil Optimization (TDO) is designed that mimics Tasmanian devil behavior in nature. The fundamental inspiration used in TDO is simulation of the feeding behavior of the Tasmanian devil, who has two strategies: attacking live prey or feeding on carrions of dead animals. The proposed TDO is described, then its mathematical modeling is presented. TDO performance in optimization is tested on a set of twenty-three standard objective functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 47 publications
0
60
0
1
Order By: Relevance
“…In this section, six recently proposed algorithms were evaluated for comparison with MRSA. These state-of-the-art algorithms are BOA [ 38 ], HHO [ 42 ], AOA [ 47 ], SSA [ 45 ], PFA [ 48 ], and TDO [ 46 ]. For a fair comparison, all the algorithm parameters are set the same as those used by the authors of the original literature, as shown in Table 13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, six recently proposed algorithms were evaluated for comparison with MRSA. These state-of-the-art algorithms are BOA [ 38 ], HHO [ 42 ], AOA [ 47 ], SSA [ 45 ], PFA [ 48 ], and TDO [ 46 ]. For a fair comparison, all the algorithm parameters are set the same as those used by the authors of the original literature, as shown in Table 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Parameters setting BOA [38] a � 0.1, c � 0.01, p � 0.6 HHO [42] β � 1.5, E 0 ∈ [− 1, 1] AOA [47] Mop max � 1, Mop min � 0.2, C � 1, a � 5, Mu � 0.499 SSA [45] c 1 � rand, c 2 � rand PFA [48] u 1 � − 1 + 2rand, u 2 � − 1 + 2rand TDO [46] ∼ 14 Computational Intelligence and Neuroscience BOA [38] HHO [42] AOA [47] SSA [45] PFA [48] TDO [46] Computational Intelligence and Neuroscience…”
Section: Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategy of pelicans in hunting and trapping prey was the main inspiration of Pelican Optimization Algorithm (POA) [36]. Some other swarm-based algorithms are: Cat and Mouse Based Optimizer (CMBO) [37], Good Bad Ugly Optimizer (GBUO) [38], Marine Predator Algorithm (MPA) [39], Tasmanian Devil Optimization (TDO) [40], Mutated Leader Algorithm (MLA) [41], Tunicate Search Algorithm (TSA) [42], Northern Goshawk Optimization (NGO) [43], Donkey Theorem Optimizer (DTO) [44], Rat Swarm Optimization (RSO) [45], All Members Based Optimizer (AMBO) [46], Red Fox Optimization (RFO) [47], Best Members Based Optimizer (MBMBO) [48], and Mixed Leader Based Optimizer (MLBO) [49].…”
Section: Lecture Reviewmentioning
confidence: 99%
“…Consequently, numerous optimization algorithms have been proposed to solve problems. Most of these algorithms are nature-inspired and widely used in engineering applications, thanks to their ability to obtain global optima and fast convergence [38][39][40][41][42]. Inspired by the lifecycle of the mouthbrooding fish, an algorithm called the Mouth Brooding Fish was developed by Jahani and Chizari in 2018 [43].…”
Section: Mouth Brooding Fish Algorithmmentioning
confidence: 99%